2018
DOI: 10.1002/cphc.201800744
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of the Benzylium and Tropylium Cations as the Two Long‐Lived Isomers of C7H7+

Abstract: Disentangling the isomeric structure of C7H7+ is a longstanding experimental issue. We report here the full mid-infrared vibrational spectrum of C7H7+ tagged with Ne obtained with infrared-predissociation spectroscopy at 10 K. Saturation depletion measurements were used to assign the contribution of benzylium and tropylium isomers and demonstrate that no other isomer is involved. Recorded spectral features compare well with density functional theory calculations. This opens perspectives for a better understand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Vibrational IR-PD spectroscopy in combination with saturation depletion measurements, facilitated by the high FELIX FEL power, allows us to quantify the isomeric ratios of ions with a specific m / q value stored in our cryogenic ion trap, as described earlier , and applied here in the case of the C 3 H 2 + isomers. In future studies, we want to use these diagnostic capabilities to optimize the formation conditions of a specific isomer in the ion source.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrational IR-PD spectroscopy in combination with saturation depletion measurements, facilitated by the high FELIX FEL power, allows us to quantify the isomeric ratios of ions with a specific m / q value stored in our cryogenic ion trap, as described earlier , and applied here in the case of the C 3 H 2 + isomers. In future studies, we want to use these diagnostic capabilities to optimize the formation conditions of a specific isomer in the ion source.…”
Section: Discussionmentioning
confidence: 99%
“…The IR spectra of the two isomers were disentangled by systematically varying the precursor (cycloheptatriene or toluene for Tr + and toluene or benzyl chloride for Bz + ) and comparing measured and calculated spectra. Jusko et al confirmed the infrared peak assignments by time-resolved depletion studies of the trapped ions . In earlier investigations, Chiavarino et al measured infrared spectra for substituted versions tropylium and benzylium cations formed from different precursors in the gas phase. , …”
mentioning
confidence: 88%
“…Experimental investigations of Tr + in the gas phase are often complicated by the coexistence of the benzylium ion (Bz + ), which is predicted to be 2760 cm –1 less stable than Tr + (see Figure and SI for details). The two species are distinguishable through their reactivity with Bz + , reacting readily with toluene through transfer of a CH 2 + unit to leave neutral benzene, whereas Tr + is relatively unreactive. , Wagner et al and Jusko et al independently reported gas-phase infrared spectra of Tr + and Bz + obtained through resonance-enhanced photodissociation (REPD) studies of mass-selected C 7 H 7 + ions tagged by Ne, Ar, or N 2 . The IR spectra of the two isomers were disentangled by systematically varying the precursor (cycloheptatriene or toluene for Tr + and toluene or benzyl chloride for Bz + ) and comparing measured and calculated spectra.…”
mentioning
confidence: 99%
“…The IRPD method allowed one to perform so-called saturation depletion measurements where specific vibrational bands of one isomeric species were fully depleted until saturation to estimate the abundance of this isomer. 37 , 39 , 40 …”
Section: Experimental and Computational Methodsmentioning
confidence: 99%